Alpha blockers should no longer be used for ureteric stones. (December 2016) - Wiseman, Oliver J.; McClinton, Sam
Abstract: Alpha-blockers have been used as medical expulsive therapy for ureteric stones for a number of years. Conventional wisdom supporting their use has recently been challenged by the publication of a large, multi-centre, randomised double-blinded, placebo-controlled study, SUSPEND, which showed that they were ineffective. This paper looks at the evidence behind the use of alpha-blockers, and discusses why we should believe the evidence we have from SUSPEND, rather than other published studies, and therefore stop using them as medical expulsive therapy. Highlights: Alpha- blockers have been used in the treatment of ureteric stones, on the basis of small single-centered studies and meta-analyses of these. SUSPEND was a large placebo-controlled, double blinded study which failed to show any benefit from using alpha-blockers in these patients. Current evidence does not support the use of this off-label treatment in the management of patients with ureteric stones.